Mexican Human Smuggling Networks in the Face of the Caravan Phenomenon - Izcara Palacios, Simón Pedro (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2024)
The debate surrounding the impact of migrant caravans on the human smuggling business in Mexico has been intense in the academia, the media and in the official discourse. The objective of this article is to examine how the caravans of Central American migrants have affected Mexican human smuggling networks. Between 2019 and 2023, in-depth interviews with 30 migrant smugglers were conducted in five Mexican States. The arrival of the caravans benefitted Mexican migrant smuggling business. Caravans have worked in favor of migrant smugglers in charge of simple networks and have benefitted smugglers leading the last link of complex networks. In contrast, some migrant smugglers operating in the southernmost areas of Mexico were left unemployed. Migrant caravans also produced a feminization of smugglers' clientele, and migrant smugglers have resort to a greater use of migrants’ displacement concealing instruments, such as the use of trucks.
Keywords: Caravans; migrant smuggling networks; migrant smugglers; Central American migrants; Mexico.